2022
DOI: 10.1038/s41413-022-00234-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in interstitial fluid flow, mass transport and the bone cell response in microgravity and normogravity

Abstract: In recent years, our scientific interest in spaceflight has grown exponentially and resulted in a thriving area of research, with hundreds of astronauts spending months of their time in space. A recent shift toward pursuing territories farther afield, aiming at near-Earth asteroids, the Moon, and Mars combined with the anticipated availability of commercial flights to space in the near future, warrants continued understanding of the human physiological processes and response mechanisms when in this extreme env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 248 publications
0
15
0
Order By: Relevance
“…This fluid flow generates a force on the surface of the implant, which is known as wall shear stress. Studies have shown that the magnitude and pattern of wall shear stress can affect the behavior of cells that come into contact with the implant surface . In areas of high shear stress, cells may align themselves along the direction of fluid flow and experience increased rates of proliferation and migration .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fluid flow generates a force on the surface of the implant, which is known as wall shear stress. Studies have shown that the magnitude and pattern of wall shear stress can affect the behavior of cells that come into contact with the implant surface . In areas of high shear stress, cells may align themselves along the direction of fluid flow and experience increased rates of proliferation and migration .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the magnitude and pattern of wall shear stress can affect the behavior of cells that come into contact with the implant surface. 32 In areas of high shear stress, cells may align themselves along the direction of fluid flow and experience increased rates of proliferation and migration. 8 Conversely, in areas of low shear stress, cells may become more round and exhibit reduced growth rates.…”
Section: Fabrication and Characterization Processmentioning
confidence: 99%
“…The reduced fluid convection rates and slower solute diffusion in microgravity could also lead to impaired heat and biomolecule exchange, potentially favoring the transport of smaller solutes. [ 70 ] Consequently, the integration of 3D bioprinted constructs into a fluidic system that drives convective flow would help to obtain the physiologically relevant environment that is needed for tissue maturation and survival.…”
Section: Current Challenges In 3d Bioprinting In Spacementioning
confidence: 99%
“…In particular, biomimetic microarchitectures can be easily imprinted or molded, and hydrogel mechanical properties can be modulated by adjusting the material concentration and crosslinking density to emulate the corresponding properties of precalcified bone (Al Hosni et al, 2022;Mao et al, 2016;Ventre & Netti, 2016). Xia et al (2022) (Grimm et al, 2016), but conversely, bone deterioration and calcium loss occurs in microgravity in the absence of constant loading (Wei et al, 2022). Loading also causes fluid movement within the canalicular system, which exerts fluid shear stress on susceptible surface molecules and cytoskeletal structures protruding from osteocytes and osteoblasts (Owan et al, 1997;Wilmoth et al, 2020).…”
Section: Substrate Deformationmentioning
confidence: 99%